2023
DOI: 10.5935/0004-2749.20230069
|View full text |Cite
|
Sign up to set email alerts
|

Ocular surface assessment and morphological alterations in meibomian glands with non-contact meibography in electronic cigarette smokers

Abstract: The study aimed to evaluate the ocular surface and meibomian gland morphology in electronic cigarette (e-cigarette) smokers. Methods: The upper and lower eyelids of 25 male e-cigarette smokers and 25 healthy male non-smoker patients were evaluated using Sirius meibography. Meibomian glands loss was automatically calculated using Phoenix meibography imaging software module, with the result obtained as percentage loss. Ocular Surface Disease Index (OSDI) questionnaire, tear breakup time test, and Schirmer II tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…This increase in tear production may be a potential homeostatic measure in response to lower tear film integrity that may result from e-cig use. In contrast, Kalayci et al [29] found that the average Schirmer II values were significantly (p = 0.002) lower in the e-cig group at 9.16 ± 2.09 mm compared to the control group at 11.2 mm ± 2.14 mm, which was attributed to the impact that the metabolites of lipid peroxidation (i.e., malondialdehyde) associated with e-cig use have on the ocular surface.…”
Section: Chronic Exposurementioning
confidence: 85%
See 4 more Smart Citations
“…This increase in tear production may be a potential homeostatic measure in response to lower tear film integrity that may result from e-cig use. In contrast, Kalayci et al [29] found that the average Schirmer II values were significantly (p = 0.002) lower in the e-cig group at 9.16 ± 2.09 mm compared to the control group at 11.2 mm ± 2.14 mm, which was attributed to the impact that the metabolites of lipid peroxidation (i.e., malondialdehyde) associated with e-cig use have on the ocular surface.…”
Section: Chronic Exposurementioning
confidence: 85%
“…Their study found that participants in the e-cig group had a significant (p = 0.002) average meibomian gland loss of 23.08 ± 6.55% on the upper eyelid and a significant (p < 0.001) average meibomian gland loss of 27.83 ± 5.98% on the lower eyelid compared to the controls who had an average loss of 17.60 ± 4.94% and 18.44 ± 5.91%, respectively. Moreover, e-cig users were more likely to have Meibomian glands that were irregularly distributed and less hyperreflective compared to the control group [29].…”
Section: Chronic Exposurementioning
confidence: 92%
See 3 more Smart Citations